Roundwood storage methods and their effect on spruce wood quality : a review - Böhm, Stephan; Solt-Rindler, Axel; Vay, Oliver; Prinz, Robert; Grabner, Michael; Kanzian, Christian (Taylor & Francis, 2026)
Climate-driven increases in calamities are altering timber supply dynamics across Europe, resulting in large volumes of spruce roundwood that cannot be processed immediately. Interim storage buffers timber supply and helps maintain wood quality. Storage decisions involve trade-offs among economic cost, environmental impact, operational feasibility and wood-quality preservation, yet the available knowledge is dispersed across technical and scientific literature. This review synthesises published research on spruce roundwood storage based on 68 studies spanning six decades. Storage methods were classified and evaluated using an integrated framework of biological, chemical and physical quality indicators. The reviewed literature shows that storage conditions, particularly the interaction of moisture availability, oxygen supply, and temperature, govern wood quality development. Dry storage is scalable but offers only short protection. Wet and anaerobic foil storage enable reliable long-term preservation but require higher technical effort. Cold storage is effective yet geographically and seasonally constrained, while live or standing storage provides limited and unpredictable preservation. Overall, no method is universally optimal, but each represents a specific preservation regime with defined operational limits. By linking storage environment to resulting wood condition, this synthesis provides a structured reference for interpreting quality development and selecting suitable storage strategies for spruce roundwood during interim storage.
Keywords: Norway spruce round timber; wood quality development; storage-induced degradation; salvage timber management